Participation, Meaningful Activity, and Social Support Among U.S. Student Service Members/Veterans. (October 2019) - Eakman, Aaron M.; Kinney, Adam R.; Reinhardt, Rebecca
Student service members/veterans (SSM/Vs) may experience diminished social support and meaningful activity due to health-related sequelae, in turn threatening their community reintegration. Social and community participation may foster both social support and meaningful activity. This study assessed whether social and community participation explained social support and meaningful activity and evaluated the psychometric properties of the Veterans' Social and Community Participation Assessment (VSCPA). Online surveys generated responses to the VSCPA, indicators of social support, meaningful activity, health-related challenges, and demographic characteristics. Multiple regression models explored predictors of social support and meaningful activity. The VSCPA comprised three components: active community participation, familial and household participation, and social participation. These components exhibited positive associations with social support and meaningful activity and negative relationships with health-related sequelae. Targeting social and community participation among SSM/Vs may be a fruitful means by which occupational therapists bolster social support and meaningful activity.